2014 International Conference on the Eleventh Industrial and Commercial Use of Energy 2014
DOI: 10.1109/icue.2014.6904178
|View full text |Cite
|
Sign up to set email alerts
|

An improved motor replacement strategy using non-intrusive motor efficiency estimation

Abstract: With increasing energy costs and a renewed focus on using energy in ways that support the environment, a structured approach is required to ensure that energy is used efficiently. Knowing the efficiency of installed motors is essential for effective motor energy management. The efficiency data can be used in the identification of opportunities for improving energy efficiency by replacing inefficient motors with highefficiency motors and improving the motor-driven processes. In this paper, a non-invasive techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Although researchers have suggested that replacing the faulty motor with an off-the-shelf high-efficiency motor would be beneficial, the high initial investment cost makes this solution quite expensive [7,8]. Furthermore, the process of replacing a SPIM often requires additional equipment or components to ensure that the purchased motor can function properly within the existing system, which can further increase the overall cost and complexity of the solution [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers have suggested that replacing the faulty motor with an off-the-shelf high-efficiency motor would be beneficial, the high initial investment cost makes this solution quite expensive [7,8]. Furthermore, the process of replacing a SPIM often requires additional equipment or components to ensure that the purchased motor can function properly within the existing system, which can further increase the overall cost and complexity of the solution [9].…”
Section: Introductionmentioning
confidence: 99%